Determinants on Generation Z's propensity to purchase sustainable products in Jakarta, Indonesia - Ichsan, Mohammad; Sutanto, Harry; Sudjatmoko, Agung; Soenarto, Hardisty Aliviasari; Salsabila, Zsa Zsa; Febioza, Muhammad Azizan (Publisher of Widyagama University of Malang (UWG Press), 2024)
Except for consumers from the Millennial and Generation Z generations, sustainable products with their primary selling point—being ecologically friendly in the business concept and the production process—have less of a place in people's purchasing preferences. Future consumers of millennials and Generation Z are committed to and interested in adopting sustainable products, which also exhibit extremely environmentally conscious consumer behavior. They will own and shape future consumption patterns. Jakartans stand out among them as particularly significant markers of economic advancement and development. This study focuses on green attitudes, social norms, and perceived behavioral control, which are thought to influence green purchase behavior through green purchase intention, in order to identify the determinant factors of green purchasing behavior toward sustainable products. A questionnaire for the non-probability sampling method was included in a Google Form package. Purchase behavior is influenced by elements from the Theory of Planned Behavior (attitude, subjective norms, and perceived behavioral control), which in turn results in sustainable product purchasing behavior. Data analysis using SmartPLS software demonstrates that purchase intention has a direct impact. The results support the benefits of sustainable product adoption patterns.JEL Classification D12; M31; Q50